2021
DOI: 10.1186/s12871-021-01412-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of analgesia with hydromorphone hydrochloride for postoperative pain following surgical repair of structural congenital malformations in children: a randomized controlled trial

Abstract: Background Effective postoperative analgesia is needed to prevent the negative effects of postoperative pain on patient outcomes. To compare the effectiveness of hydromorphone hydrochloride and sufentanil, combined with flurbiprofen axetil, for postoperative analgesia in pediatric patients. Methods This prospective randomized controlled trial included 222 pediatric patients scheduled for repair of a structural congenital malformation under general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Tramadol was previously considered a safe and effective postoperative analgesia, and was widely used for pediatric postoperative pain treatment. Hullett et al 8 found that tramadol was a suitable drug for children undergoing adenotonsillectomy for obstructive sleep apnea. Ozalevli et al 9 also found that intravenous patient‐controlled tramadol is an alternative to patient‐controlled morphine for postoperative pain relief in children after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol was previously considered a safe and effective postoperative analgesia, and was widely used for pediatric postoperative pain treatment. Hullett et al 8 found that tramadol was a suitable drug for children undergoing adenotonsillectomy for obstructive sleep apnea. Ozalevli et al 9 also found that intravenous patient‐controlled tramadol is an alternative to patient‐controlled morphine for postoperative pain relief in children after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In children, the efficacy of hydromorphone to treat perioperative pain has been demonstrated in a small number of studies when administered IV, either in bolus, continuous or PCA ( 14 , 43 , 54 60 ). The efficacy of epidural administration has also been established ( 61 67 ) and a recent study showed the efficacy of intranasal administration ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies, whatever the route of administration, primarily included children and adolescents. Only two of them included infants ( 54 , 59 ). These studies showed good tolerance of hydromorphone in infants, children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…If the FLACC or NRS score remained ≥ 4 after three or more PCA compressions, a remedy of 0.2 mg/kg ketorolac tromethamine was administered to enhance analgesia. The Ramsey Sedation Scale is one of the commonly used methods to assess the level of perioperative sedation in children [ 13 15 ]. Therefore, Ramsey Sedation Scale was used in this study to assess the level of postoperative sedation.…”
Section: Methodsmentioning
confidence: 99%